Solve the following :   $37+ (-2) (-65) + (-8) $


Given :

 $37+ (-2) (-65) + (-8) $


To do:

We have to find the sum of the given numbers.


Solution:

Solving by BODMAS rule,

$(-2) (-65)$

$ -2 \times - 65  = 130 $                              [$- \times - = +$]

$+ (-8) = -8 $                                             [$+ \times - = -$]

$37 + 130 - 8$

$ = 167 - 8 $

$ = 159$

Therefore, the sum of given number is , $37+ (-2) (-65) + (-8)  = 159$.

Tutorialspoint
Tutorialspoint

Simply Easy Learning

Updated on: 10-Oct-2022

341 Views

Kickstart Your Career

Get certified by completing the course

Get Started
Advertisements